Exploring the role of social capital in enhancing economic activity among poor households - Faisal, Achmad; Ali, M Saleh S; Rahmadanih,; Lakare, Heliawaty Ch (Asian Development Policy Review, 2025)
Alleviating household economic challenges and poverty remains a global priority in the pursuit of national well-being. This study argues that fostering sustainable social capital can enhance the economic resilience of poor households. Therefore, this study aimed to explore the role of social capital in the economic activities of poor households. A qualitative method with a phenomenological approach was employed, using observations and in-depth interviews with 18 purposively selected respondents from both rural-agricultural and urban-multi-sector areas in Enrekang Regency, Indonesia. The findings revealed that social capital significantly influenced all three aspects, particularly through the utilization of social relationships, trust, networks, and norms. Poor households relied on these social connections such as family ties, friendships, and community networks to access critical resources, including informal loans, market information, and employment or business opportunities. These networks helped households navigate financial constraints and gain access to markets for their products. In conclusion, social capital played a crucial role in mitigating economic uncertainty and reducing everyday risks for poor households. Interestingly, the study found that regional context (rural and urban) did not significantly affect how social capital was utilized. Instead, variations were more closely linked to the diversity of economic activities across different household groups.